Optimum layouts of a cluster of heaving point absorbers in front of a wall - Loukogeorgaki, Eva; Michailides, Constantine; Lavidas, George; Chatjigeorgiou, Ioannis K. (My University, 2021)
In this paper, we determine optimum layouts of a cluster of oblate spheroidal heaving point absorbers in front of a wall, that maximize the annual averaged power absorbed by the cluster, while satisfying specific spatial constraints. An iterative optimization process is developed by coupling a hydrodynamic model with a genetic algorithms solver. Optimization is performed for three near-shore sites in the Aegean Sea, Greece. Optimum layouts are obtained considering part of or the whole wall length, available for the PAs’ sitting. The effect of the incident wave direction on the optimum layouts’ formation and the absorbed power is also assessed. Finally, the dependence of the maximized absorbed power upon the deployment site is illustrated.
Keywords: Clusters; Genetic algorithms; Layout; Optimization; Point absorbers; Wall; Wave energy